If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16m + -15m = -15 Combine like terms: 16m + -15m = 1m 1m = -15 Solving 1m = -15 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '1'. m = -15 Simplifying m = -15
| x^3+x^2-19x+30=0 | | q/-0.w=15.4 | | 4/5/x=16/35 | | -14r-10r+13r=11 | | 4kx7g/k-4h | | 2x+4+3x=5(x-1) | | d/=20.8 | | -8(1-3b)-(3b+2)=32 | | 10+78=55 | | -r-10= | | 6x^2=-35-31x | | d/9.7=w0.8 | | 120/3/4-12=x | | x^2=9yk | | -3(8-5n)-8(1+5n)=-32 | | -99=-6c | | 13x-11x-x=14 | | 6(v+8)-7(v-4)=72 | | 4x^2=9yk | | 6-7x=29 | | 120*3/4-12=x | | -8y=x | | -6(r+1)+2(7r-7)=-20 | | 5x-3+2=2x+11 | | 15p+p=-12p+7 | | 14c-8c-5c+2c-2c=18 | | 8(-8r-1)-(2r-8)=-66 | | x=2x^2-18 | | log(x+14)+log(x+134)=4 | | 34,5=z/70 | | 7t-13t+-9+20t=-20 | | e^x/(x^3) |